The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1037/hea0000558
|View full text |Cite
|
Sign up to set email alerts
|

How do tobacco power walls influence adolescents? A study of mediating mechanisms.

Abstract: The tobacco power wall increases adolescents' smoking risk, and this effect is partly explained by the effect of the power wall on adolescents' perceptions of how normative smoking is. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…The current study advances our understanding of how exposure to the tobacco power wall—in its current, minimally-regulated form—may affect adolescents’ susceptibility to smoke in the future. Although prior studies had demonstrated a causal association between exposure to the tobacco power wall and adolescents’ risk for smoking (Shadel et al, 2016) and established perceived smoking norms as mediator of that association (Setodji et al, 2018), it was unclear until now whether those associations depend on youth paying a minimum amount of attention to the power wall or if the mere presence of the power wall is sufficient for it to impact susceptibility. That attention to the tobacco power wall was positively associated with susceptibility to future smoking susceptibility in this study suggests that policies aimed at decreasing the salience of power walls in retail outlets, e.g., locating the power wall elsewhere in the POS environment or reducing the size or volume of displayed products, should be given strong consideration as strategies for mitigating the impact of in-store displays on adolescent smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study advances our understanding of how exposure to the tobacco power wall—in its current, minimally-regulated form—may affect adolescents’ susceptibility to smoke in the future. Although prior studies had demonstrated a causal association between exposure to the tobacco power wall and adolescents’ risk for smoking (Shadel et al, 2016) and established perceived smoking norms as mediator of that association (Setodji et al, 2018), it was unclear until now whether those associations depend on youth paying a minimum amount of attention to the power wall or if the mere presence of the power wall is sufficient for it to impact susceptibility. That attention to the tobacco power wall was positively associated with susceptibility to future smoking susceptibility in this study suggests that policies aimed at decreasing the salience of power walls in retail outlets, e.g., locating the power wall elsewhere in the POS environment or reducing the size or volume of displayed products, should be given strong consideration as strategies for mitigating the impact of in-store displays on adolescent smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to POS tobacco displays is known to be associated with both adolescent smoking and susceptibility to future smoking (Paynter & Edwards, 2009; Robertson, McGee, Marsh, & Hoek, 2015; Shadel, Martino, Setodji, Scharf, Kusuke, Sicker, & Gong, 2016). Studies that have attempted to identify the mechanisms by which exposure to POS tobacco displays might affect young people’s susceptibility for use have focused on perceptions of the attractiveness of cigarette packs, smoking-related norms, and the perceived accessibility of cigarettes (McNeill et al, 2011; Setodji, Martino, Gong, Dunbar, Kusuke, Sicker, & Shadel, 2018; Wakefield, Germain, Durkin, & Henriksen, 2006), all factors that are known to increase the likelihood of smoking (Doubeni, Li, Fouayzi, & DiFranza, 2008; Germain, Wakefield, & Durkin, 2010; Olds, Thombs, & Tomasek, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this investigation is that the calculation for SAV did not incorporate product displays, which have been shown to influence adolescent smoking. 50 Similarly, the calculation was restricted to the SAV among tobacco products rather than the SAV among all products. It is also important to remember that the sample was limited to at-risk adolescents in southern California who were predominantly Hispanic (75.6%).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Naturalistic settings-such as bar laboratories-are frequently used in alcohol consumption research to mimic typical drinking environments [26]. Recently, artificial shopping laboratories have been used to study tobacco [27,28] and sugar-sweetened beverage purchasing behaviour, with HWLs reducing the likelihood of purchasing these drinks [29]. Such settings provide greater ecological validity than studies conducted online.…”
Section: Introductionmentioning
confidence: 99%